Peningkatan Ekonomi Paska-Pandemi Melalui Pengembangan Ulat Hongkong pada Kelompok Masyarakat Pembudidaya Ikan Air Tawar “Sumber Duren” Kabupaten Malang: Enhanching Post-Pandemic Economic Recovery Through the Development of Mealworm Cultivation in Community Group of “Sumber Duren”, Freshwater Fish Cultivator, Malang Regency - Nursyam, Happy; Yufidasari, Hefti Salis; Astuti, Retno Tri; Setijawati, Dwi; Meitasari, Deny; Septian, Wike Andre; Hussein, Naufal Amirudin; Ash-Syufi, Abdillah Hanan; Septiansyah, Farhan Amar; Kuntowibisono, Eduardus; Raihannisa, Widi; Putra, Azriel Zharif Adha Ekta; Febriansyah, Zulfikri; Dharma, Syahrizal Bima Satya; Sembiring, Dariyus DC (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Senggreng Village is one of the areas in Sumber Pucung District, Malang Regency, promising to be developed in agriculture, animal husbandry, fisheries, and agro-tourism. Abundant water resources mainly support the fisheries and agriculture potency due to its position near the Sutami Dam. One of the community groups in Senggreng Village, "Sumber Duren", is "engaged in developing a small amusement park that integrates culinary, fishing park and freshwater fish farming business, managed through a cage system. Regardless of its considerable potency, fish farming has not been carried out intensively, especially due to the high prices of commercial fish feed. Therefore, this community service team proposed a solution by initiating mealworm (Tenebrio molitor) cultivation as a cheap, high-protein, and sustainable source of fish feed to increase crop yields. Experienced mealworm practitioners also provided intensive mealworm cultivation education, training, and profitable business planning. Through this program, the community group "Sumber Duren" has been" successful in cultivating mealworms starting from the seedling phase to becoming broodstock and laying eggs. Based on the questionnaire data collection, most community group members stated that this community service activity helped provide new knowledge interested in cultivating alternative feeds, and 80% of respondents expected the activity to continue in the following years.